Analysis of Essential Oil of Juniperus communis and Terpenoids Dried Fruits From Golestan of Iran - Rezvani, Sahar (Asian Journal of Chemistry, 2010)
The essential oil extracts of juniper oil (Juniperus communis) were studied. The oils consisted mainly of monoterpene hydrocarbons. Analysis of essentials oil, from dried fruits was detected after disitillation by GC-MS.The results indicated that effeciacious materials of this plant were different, significantly. A total 27 compounds from Juniperus communis were detecte and the GC/MS analysis showed that the main compounds in the oil were α-pinene (46.63 %) and α- cedrol (12.36 %), Δ-3-carene (9.85 %), α-terpinolene (4.64 %) and terpin-4-ol (2.86 %).